Differences in diagnostic patterns of obstructive airway disease between areas and sex in Sweden and Finland-the Nordic EpiLung study - Axelsson, Malin; Ilmarinen, Pinja; Backman, Helena; Ekerljung, Linda; Hedman, Linnea; Langhammer, Arnulf; Lindberg, Anne; Lindqvist, Ari; Nwaru, Bright I.; Pallasaho, Paula; Sovijärvi, Anssi; Vähätalo, Iida; et al. (Journal of Asthma, 2023)
Objective:To investigate the current prevalence of physician-diagnosed obstructive airway diseases by respiratory symptoms and by sex in Sweden and Finland. Method:In 2016, a postal questionnaire was answered by 34,072 randomly selected adults in four study areas: Vastra Gotaland and Norrbotten in Sweden, and Seinajoki-Vaasa and Helsinki in Finland. Results:The prevalence of asthma symptoms was higher in Norrbotten (13.2%), Seinajoki-Vaasa (14.8%) and Helsinki (14.4%) than in Vastra Gotaland (10.7%), and physician-diagnosed asthma was highest in Norrbotten (13.0%) and least in Vastra Gotaland (10.1%). Chronic productive cough was most common in the Finnish areas (7.7-8.2% versus 6.3-6.7%) while the prevalence of physician-diagnosed chronic bronchitis (CB) or chronic obstructive pulmonary disease (COPD) varied between 1.7 and 2.7% in the four areas. Among individuals with respiratory symptoms, the prevalence of asthma was most common in Norrbotten, while a diagnosis of COPD or CB was most common in Vastra Gotaland and Seinajoki-Vaasa. More women than men with respiratory symptoms reported a diagnosis of asthma in Sweden and Seinajoki-Vaasa but there were no sex differences in Helsinki. In Sweden, more women than men with symptoms of cough or phlegm reported a diagnosis of CB or COPD, while in Finland the opposite was found. Conclusion:The prevalence of respiratory symptoms and corresponding diagnoses varied between and within the countries. The proportion reporting a diagnosis of obstructive airway disease among individuals with respiratory symptoms varied, indicating differences in diagnostic patterns both between areas and by sex. Peer reviewed